PENGARUH FITUR APLIKASI BLACKBERRY MESSENGER (BBM) PADA ANDROID DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE BERBASIS ANDROID - MOHAMMAD FIKRI AMRULLAH (Jurnal Manajerial, 2018)
This research aims to identify the factors that influence the purchase decision based on Android Smartphone Students study at Muhammadiyah University of Gresik . This study used a sample of 80 respondents , the type of data used primer.Experiance also test two independent variables , namely fuel and Lifestyle Features that affect the purchase decision . The purpose of this study presented was to determine the effect of lifestyle features and the purchase intention android based smartphone by using linear regression analysis bergand . The results showed that the fuel features significantly influence the purchase decision android based smartphone